Authentication-based double images fractal watermarking model of vector maps - SUN Jian-guo1; MEN Chao-guang1; MA Chun-guang1; LI Cheng-ming2 (Tongxin xuebao)
To realize the invasion identification and copyright authentication, a novel digital watermarking model for vector maps based on authentication was introduced.A double images fractal coding technology was proposed for the compound images, namely, the map owner’s fingerprint was taken as the domain blocks and the vector map was taken as range blocks.The control parameters of fractal similarity computation were defined as watermarking, which could be embedded into the properties file of the map.Experiments and analysis show that, besides providing services of copyright protection, the model improves the robustness and the owners’ authentication probability.